Catastrophes and the apocalyptic in the Middle Ages and the Renaissance - Bjork, Robert E. (Arizona studies in the Middle Ages and the Renaissance, 2019)
"This collection of essays treats the topic of catastrophes and their connection to apocalyptic mentalities and rhetoric in the Middle Ages and the Renaissance, both in Europe and in the Muslim world. In the twenty-first century, insurance companies still refer to ‘acts of God’ for any accident or event not influenced by human beings: hurricanes, floods, hail, tsunamis, wildfires, earthquakes, tornados, lightning strikes, even falling trees. The remote origin of this concept can be traced to the Hebrew Bible. During the Second Temple period of Judaism a new literary form developed called ‘apocalyptic’ as a mediated revelation of heavenly secrets to a human sage concerning messages that could be cosmological, speculative, historical, teleological, or moral. The best-known development of this type of literature, however, came to fruition in the New Testament and is, of course, the Book of Revelation, attributed to the apostle John, and which figures prominently in the Middle Ages and Renaissance. This collection of essays, the result of the 2014 ACMRS Conference, treats the topic of catastrophes and their connection to apocalyptic mentalities and rhetoric in the Middle Ages and the Renaissance (with particular reference to reception of the Book of Revelation), both in Europe and in the Muslim world. The twelve authors contributing to this volume use terms that are simultaneously helpful and ambiguous for a whole range of phenomena and appraisal."